Quality Assessment and Host Preference of Telenomus podisi (Hymenoptera: Scelionidae) for Fresh and Cryopreserved Euschistus heros (Hemiptera: Pentatomidae) Eggs - Gabryele Silva Ramos; Rafael Hayashida; Pedro Hiroshi Passos Ikuno; Vanessa Rafaela de Carvalho; William Wyatt Hoback; Regiane Cristina de Oliveira (Insects)
The development of the mass rearing technique for the egg parasitoid Telenomus podisi has been under study for about 20 years, with increasing attention on the development of quality control. Here, we evaluated the behavior, biological parameters, morphometrics and presence of endosymbionts of T. podisi produced in cryopreserved eggs compared to those produced in traditional fresh stink bug eggs. Parasitoids reared from cryopreserved eggs showed similar parasitism and emergence rates, sex ratios, longevity, morphometrics, and proportions of flyers compared to those originating from fresh eggs. Slight differences, including an increase in egg-to-adult development time and differences in the presence of endosymbionts, were observed. Despite these differences, we conclude that the use of cryopreserved eggs is suitable for T. podisi mass rearing, allowing more options for timed inundative parasitoid releases for biological control.